PENGARUH PEMBIAYAAN BERMASALAH DAN LIKUIDITAS TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH KABUPATEN BOGOR STUDI DATA OTORITAS JASA KEUANGAN TAHUN 2017-2019 - Lukman Hakim; Tubagus Rifqy Thantawi; Miftakhul Anwar (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This study aims to determine the effect of Non-Performing Financing (NPF) and Liquidity (CR) Profitability (ROA) in BPRS Bogor Regency for the 2017-2019 Period Financial Review of Service Authority Data (OJK). The samples used in this study were 48 samples. Collecting data in this study using purfosive sampling method with the understanding that the data collected is predetermined data. The data analysis technique used is multiple linear regression analysis. The results of this analysis indicate that NPF and CR have a significant effect on ROA.